Ability of Certain Clays in Decolarization of Lubricant Oil - Karim1, Abdulsalam R.; Jubrail, Karim J.; Abdullah1, Mohhamad A. (Sulaimani Journal for Pure and Applied Sciences, 2005)
Various types of clays (namely, yellow bentonite, brown bentonite, and Kaolin) of Iraqi Kurdistan have been used for decolorizing dark oils and compared with activated China clay and Iranian clay called (Rose); which are largely used for the industriai processing of mineral oils. Chemical analysis has been made for all clay saniples for determination of their chemical compositions then different amounts (percentage) ofeach clay (3-11%iviv) have been used lor the decolorizing process ofthe lubricant oil, that manufactured at Sulaimani city at tixed temperature and particle size. Later, studies of different temperatures (150,200.250,300"C) at fixed amount of clay have been carried out to show the temperature effect on adsorption process. The decolorizing efficiency' of clays was found to be in the following order; China clay, Iranian clay. Kaolin. yellow clay , brown clay. Also the effecl of acid has been studied to activate and improve the adsorption process in the decolorization ol dark lubricant oil. The adsorption isotherms data obtained rvere found to follow the Freundiich adsorption isotherm model.
Keywords: Bentonite; Kaolin; bleaching; mineral oil; adsorption